Android tablets for dummies ebook - Gookin, Dan (2013)
Get the most out of your Android tablet with this full-color reference Whether you are one of the millions who already have an Android tablet, or you are interested in joining the masses with a first-time purchase, this friendly guide is perfect for you! Written by the ultimate For Dummies author Dan Gookin, this funny-but-informative book introduces you to the features of all Android tablets and details the nuances of what makes a tablet more than a smartphone yet different than a computer. You'll discover how to browse the web on your tablet, get organized with a digital calendar, enjoy music and books, use the camera, access social networks, watch video, and more. Helps you choose the right apps for all your interests out of the thousands of apps that are available for the Android platform Covers all Android tablets, from popular favorites like the Kindle Fire HD, NOOK HD, and Google Nexus to devices from other manufacturers like Samsung, Asus, Motorola, and others Walks you through maintenance and common troubleshooting tips Packed with invaluable information on everything from typing and editing text to customizing and personalizing your tablet, Android Tablets For Dummies gets you off the ground running with your Android tablet!